Experiences with breast cancer: A study between Brazilian and German women - Maristela Júlia Fernandes; Luciana Kind (Estudos de Psicologia (Campinas), 2023)
Abstract Objective This study aimed to identify the experiences of women from two different countries, through the discovery and treatments of breast neoplasms, highlighting the phenomenon based on relationships with socio-cultural aspects. Method The Grounded Theory was the theoretical and methodological tool for data collection and analysis, in this qualitative research of which 15 Brazilian women (35-65 years old) and 12 German women (50-81 years old) participated, all in treatment for breast cancer. Results The results revealed differences in obtaining the diagnosis – in Brazil mostly sought from selfexamination, and in Germany, for complying with the invitation letter for mammography. The disease’s disclosure pointed out that cancer’s stigmas are more significant among German women than Brazilian women. Conclusion Differences between prescribed treatments reveal that Brazilian women receive more chemotherapies, and German women, radiotherapies. Finally, it is considered that some women’s attitudes bring gains and decrease suffering, while others, losses, and stigmatization.